Should antioxidant vitamin supplementation be applied in patients with metabolic syndrome? A case-control study - Godala, Małgorzata; Materek-Kuśmierkiewicz, Izabela; Moczulski, Dariusz; Szatko, Franciszek; Gaszyńska, Ewelina; Tokarski, Sławomir; Kowalski, Jan (Menopause Review/Przegląd Menopauzalny, 2016)
Introduction : All cells in the human body are exposed to reactive oxygen species (ROS), which disturb the metabolic reactions in the organism. The antioxidant system in the human body consists of enzymatic and non-enzymatic mechanisms, among which vitamins A, C, and E play a major role. The aim of the study was to evaluate the supply of vitamins A, C, and E from daily food rations (DFR) in postmenopausal women with metabolic syndrome (MS) in relation to current nutrition standards. Material and methods: The study involved 184 women with MS, aged 45-68 years (mean 57.38 ±8.17 years). The control group comprised 90 women, aged 41-65 years (mean 57.48 ±5.79 years) without MS. The food intake was assessed using 24-hour dietary recalls. Results: The evaluation of intake of vitamins measured with daily food rations (DFR) demonstrated that the optimal level of 90-110% according to standards was achieved only in 3.62% of women with metabolic syndrome for vitamin A, in 8.88% for vitamin C, and in 11.41% for vitamin E, which was significantly less often found than in the control group (p < 0.001). Conclusions : Women with MS are characterised by diversified intake of vitamins A, C and E, and a subgroup of this patients present low level of antioxidant vitamins intake. Supplementation with antioxidant vitamins should be prescribed individually to postmenopausal women with MS.